2003
DOI: 10.1021/ol0341849
|View full text |Cite
|
Sign up to set email alerts
|

Di-2-pyridylmethylamine-Based Palladium Complexes as New Catalysts for Heck, Suzuki, and Sonogashira Reactions in Organic and Aqueous Solvents

Abstract: A new palladium-dipyridylmethylamine complex is an excellent catalyst for C-C bond-forming processes such as the Heck, Suzuki, and Sonogashira reactions in organic and aqueous solvents under homogeneous conditions. [reaction: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 294 publications
(93 citation statements)
references
References 32 publications
1
87
0
1
Order By: Relevance
“…The corresponding palladium(II) chloride complexes 4a and 4b were obtained in 73 and 94% yield after reaction of ligands 6 with fresh prepared H 2 PdCl 4 (Scheme 1). [17] These complexes 4a and 4b showed a low solubility in most organic solvents and their NMR spectra revealed a mixture of conformational isomers I and II (Figure 2) in 6 : 1 and 3 : 1 ratios, respectively. Both isomers interconverted when complex 4a was heated to 56 8C in DMSO-d 6 in an NMR tube.…”
Section: Synthesis Of Di(2-pyridyl)methylamine-derived Palladium Compmentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding palladium(II) chloride complexes 4a and 4b were obtained in 73 and 94% yield after reaction of ligands 6 with fresh prepared H 2 PdCl 4 (Scheme 1). [17] These complexes 4a and 4b showed a low solubility in most organic solvents and their NMR spectra revealed a mixture of conformational isomers I and II (Figure 2) in 6 : 1 and 3 : 1 ratios, respectively. Both isomers interconverted when complex 4a was heated to 56 8C in DMSO-d 6 in an NMR tube.…”
Section: Synthesis Of Di(2-pyridyl)methylamine-derived Palladium Compmentioning
confidence: 99%
“…[16] Very recently, as part of our studies to find robust and easily prepared systems to catalyze C À C bond forming reactions, we have communicated that di(2-pyridyl)methylamine-derived palladium(II) chloride complexes 4 with less electron-rich ligands are very active homogeneous catalysts for Heck, Suzuki and Sonogashira couplings in organic and aqueous solvents. [17] We report here the scope of this type of catalyst in homogeneous SuzukiMiyaura reactions between bromo-or chloroarenes and arylboronic acids in water and aqueous solvents. In addition, related C(sp 3 ) À C(sp 2 ) bond formation reactions in water between alkylboronic acids and aryl halides and between arylboronic acids and benzylic chlorides and allylic substrates are also discussed.…”
Section: Introductionmentioning
confidence: 99%
“…196 Interestingly, the air-stable ligand 108 could be recovered by chromatography on silica gel and reused. Nájera et al 197 recently reported that the dipyridylmethylamine-based Pd(II) complex 109 ( Figure 18) is able to promote the reaction of aryl halides with phenylboronic acid and that the coupling involving aryl chlorides has to be run in the presence of TBAB as an additive.…”
Section: Figure 17mentioning
confidence: 99%
“…The use of water as a solvent in Pd-catalyzed reactions has gained increasing attention during last years [7] due to the environmental and economic benefits of replacing organic solvents by water as well as its interesting chemical properties, including high polarity and strong hydrogen-bonding ability, among others. However, using water as solvent, mostly aryl iodides [8] and bromides [9] have been used as coupling partners and only a few reports can be found in the literature on the successful coupling of activated aryl chlorides. [5,10] In recent years, we have demonstrated the high activity of oxime palladacycles…”
Section: Introductionmentioning
confidence: 99%